Multi-epitope vaccines: a promising strategy against viral diseases in swine - Chen, Xiaowei; Li, Yongfeng; Wang, Xiao (Frontiers in Cellular and Infection Microbiology, 2024)
Viral infections in swine, such as African swine fever (ASF), porcine reproductive and respiratory syndrome (PRRS), and foot-and-mouth disease (FMD), have a significant impact on the swine industry. Despite the significant progress in the recent efforts to develop effective vaccines against viral diseases in swine, the search for new protective vaccination strategy remains a challenge. The antigenic epitope, acting as a fundamental unit, can initiate either a cellular or humoral immune response. Consequently, the combination of multi-epitopes expressing different stages of viral life cycle has become an optimal strategy for acquiring a potent, safe, and effective vaccine for preventing and treating viral diseases in swine. Recent progresses in immunoinformatic tools, coupled with an understanding of host immune responses and computational biology, have paved the way for innovative vaccine design disciplines that focus on computer-assisted, in-silico epitope prediction for the prevention of viral diseases in swine. The concept of multi-epitope vaccines driven by immunoinformatic methods has gained prominence in multiple studies, particularly in the development of vaccines targeting conserved epitopes in variable or rapidly mutating pathogens such as African swine fever virus (ASFV) and porcine reproductive and respiratory syndrome virus (PRRSV). In this review, we provide an overview of the in-silico design of the multi-epitope vaccines against viral diseases in swine, including the antigenicity, structural quality analysis, immune simulations, and molecular dynamics (MD) simulations. Furthermore, we also enumerate several multi-epitope vaccine applications that have shown promise to be against viral diseases in swine.